Love lies - Parks, Adele (New York : Berkley Books, 2009)
Who killed suburban wife and mother Nancy Cooper? Suspicion fell on Nancy's handsome husband, Brad. But why would a devoted husband and father of two young girls want to kill his wife? Nancy's parents and friends knew why.
"A true story of marriage and murder in the suburbs"--Cover.
Keywords: Cooper, Nancy, -- 1973-2008.; Homicide investigation -- North Carolina -- Cary -- Case studies; Trials (Murder) -- North Carolina -- Cary